Scaphium affine Ethanol Extract Induces Anoikis by Regulating the EGFR/Akt Pathway in HCT116 Colorectal Cancer Cells - Kawk, Hye Won; Nam, Gun-He; Kim, Myeong Jin; Kim, Sang-Yong; Kim, Young-Min (Frontiers in Oncology, 2021)
Scaphium affine ethanol extracts (SAE) is a species that has been shown to contain various physiological effects; however, its anticancer effects have yet to be revealed. We qualitatively evaluated β-sitosterol in SAE through high-performance liquid chromatography (HPLC). The cytotoxicity in HCT116 and HT29 colorectal cancer cells and CCD841 normal colon cells was confirmed through WST-1 assays. Selective cytotoxicity was observed in colorectal cancer cells, with greater cytotoxicity demonstrated in the HCT116 cell line. As such, the HCT116 colorectal cell line was selected for subsequent experiments. After HCT116 cells were treated with SAE, it was confirmed that the apoptosis rate was increased in a SAE dose-dependent manner through Annexin V assay. SAE further showed dose-dependent suppression of invasion through invasion assays. Anoikis induction through the EGFR/Akt pathway in HCT116 colorectal cancer cells was confirmed by Western blotting. The tumor suppressive effects of SAE was assessed in vivo using a xenograft model of human HCT116 colorectal cancer cells. As a result, we confirmed that SAE decreased tumor size in a dose-dependent manner and that p-EGFR and cleaved-caspase 3 in tumors were also regulated in a dose-dependent manner. This study showed that SAE, by containing β-sitosterol with proven anticancer effects, induces anoikis through the EGFR/Akt pathway in HCT116 colorectal cancer cells both in vitro and in vivo.